REGULATIONS FOR WASTE MANAGEMENT OF DISPOSABLE MASK DURING THE COVID-19 PANDEMIC - Maria Novita Apriyani; Aldira Mara Ditta Caesar Purwanto (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2021)
Corona Virus Disease 2019 that has not ended, has an impact including the use of disposable masks in the world is increasing. Although there are calls to use masks such as cloth masks to coat medical masks when doing U.S. actives outside the home, in fact the public prefers to use disposable medical masks. Disposable masks are feared to be more and more in number if not managed properly. The issues studied in this scientific article are the settings related to the management of disposable mask waste and the implications of waste management of disposable mask in the community. This research method uses juridical-normative writing methods with a statutory approach. The result of this study is the waste management of disposable medical masks entering the realm of special arrangements (lex specialists) consisting of guidelines of the Ministry of Environment and Forestry of the Republic of Indonesia and the Ministry of Health of the Republic of Indonesia.Waste management of disposable medical masks can be done with a thorough approach when a product produced in the community is indicated as waste until the product has been managed in landfill so that the output of waste management becomes environmentally friendly by using a new approach. through the activities of waste management of medical masks used in the community in accordance with existing guidelines.